Evaluation of the relationship between serum anti TPO antibody levels and mood disorders in euthyroid pregnant women. (1st October 2020) - Kashanian, Maryam; BozorgzadehVostaKolaei, Shabnam; Naderi, Zahra; EftekharArdebili, Mehrdad; Sheikhansari, Narges; Javanmanesh, Forough
Abstract: Introduction: Depression and anxiety during pregnancy have a negative impact on prenatal health and reduces mother's child care capability. Up to 20% of the pregnant women experience mood disorders. Objective: The aim of this study was evaluating the relationship between serum anti-TPO antibody levels and mood disorders in pregnant euthyroid women. Materials and methods: Serum anti-TPO antibody levels were measured in the first trimester of gestation in euthyroid pregnant women. Then, the women were divided into two groups of positive and negative anti-TPO antibody. Depression and anxiety were evaluated by Hamilton depression rating scale (HAM-D) and Hamilton anxiety rating scale (HAM-A) during the first, second, and third trimester of pregnancy (all women had three assessments during pregnancy). Results: Thirty women with high serum anti-TPO antibody levels (case group) and 32 women with normal serum anti-TPO antibody levels (control group) were compared. Mean anti-TPO levels were 105.63 ± 54.17 and 5.57 ± 1.80 IU/mL in case and control groups, respectively ( p = .000). The baseline characteristics and initial HAM-A and HAM-D scores were not significantly different in the two groups except for anti-TPO. Pair t -test showed that the level of anxiety and depression has increased significantly during pregnancy in both groups. Comparison of anxiety and depression level in both groups showed that in anti-TPO antibody positive group, anxiety, and depression levels were significantly higher than the anti-TPO antibody negative group. Conclusion: Depression and anxiety of euthyroid pregnant women in the second and third trimester of pregnancy have a significant correlation with serum anti-TPO antibody levels of the first trimester of pregnancy.